Factors Affecting the Achievement of Food Consumption Patterns of Agritourism Workers - Nur Sabrina Alfain; Sugiyanto Sugiyanto; Edi Dwi Cahyono; Keppi Sukesi; Asihing Kustanti (The University of Lampung, 2025)
Household food consumption pattern is a habit or way of a family in choosing, processing, and consuming food daily. This pattern reflects the type, amount and quality of food consumed in a household. The problem that often occurs in household food consumption patterns is the imbalance of nutritional intake, which can be influenced by various factors both from socio-demographic and socio-economic factors. This study was conducted to analyze the achievement of household consumption patterns of agritourism workers and analyze what factors affect the achievement of household consumption patterns. The method used to analyze the achievement of food consumption patterns is through the calculation of EAR, PAR, DDP score, while for the analysis of influential factors using the ordinal logistic regression method with the help of SPSS 30 software. The results of the study explained that the EAR of agritourism worker households in Betet Village was 1946.37 kcal/cap/day or 92.68%EAR. Meanwhile, the PAR of tourist worker households in Betet Village was 53.52 grams/cap/day or 93.89%PAR and the DDP score was 93.16. Factors that influence EAR are the age of the housewife, the level of education of the housewife and the number of family members. While the factors that influence PAR are the age of the wife and household income. Keywords: Desirable Dietary Pattern (DDP), Ecotourism, Energy Adequacy Rate (EAR), Protein Adequacy Rate (PAR).